2014
DOI: 10.1002/cmdc.201402290
|View full text |Cite
|
Sign up to set email alerts
|

Stimuli‐Responsive Polymeric Nanoparticles for Nanomedicine

Abstract: Nature continues to be the ultimate in nanotechnology, where polymeric nanometer-scale architectures play a central role in biological systems. Inspired by the way nature forms functional supramolecular assemblies, researchers are trying to make nanostructures and to incorporate these into macrostructures as nature does. Recent advances and progress in nanoscience have demonstrated the great potential that nanomaterials have for applications in healthcare. In the realm of drug delivery, nanomaterials have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
65
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(71 citation statements)
references
References 178 publications
(51 reference statements)
1
65
0
3
Order By: Relevance
“…First, they hold high stability and good biocompatibility both in vitro and in vivo , and can solubilize a wide range of poorly soluble drugs. Polymeric nanoparticles are commonly prepared from natural polymers (such as chitosan) or synthetic biocompatible polymers [such as poly-lactic-co-glycolic acid (PLGA)], while liposomes, analogs of biological membranes, have always been regarded as one of the most biocompatible vehicles for drug delivery (Colson and Grinstaff, 2012; Hadinoto et al, 2013; Mandal et al, 2013; Crucho, 2015). In addition, polyethylene glycol (PEG) is usually conjugated to the polymer nanoparticles to enhance the immune-compatibility.…”
Section: Organic Nanoparticles For Targeting Cscsmentioning
confidence: 99%
“…First, they hold high stability and good biocompatibility both in vitro and in vivo , and can solubilize a wide range of poorly soluble drugs. Polymeric nanoparticles are commonly prepared from natural polymers (such as chitosan) or synthetic biocompatible polymers [such as poly-lactic-co-glycolic acid (PLGA)], while liposomes, analogs of biological membranes, have always been regarded as one of the most biocompatible vehicles for drug delivery (Colson and Grinstaff, 2012; Hadinoto et al, 2013; Mandal et al, 2013; Crucho, 2015). In addition, polyethylene glycol (PEG) is usually conjugated to the polymer nanoparticles to enhance the immune-compatibility.…”
Section: Organic Nanoparticles For Targeting Cscsmentioning
confidence: 99%
“…PEG and PEI are also functionalized through amine, carboxylic acids or maleimide groups to peptides, antibodies or any other ligands for active targeting [71,157,158]. Several liposomal formulations for cancer therapy have been approved by the Food and Drug Administration (FDA) [159,160], and have shown promising results in preclinical and clinical studies for drug delivery [150,161,162]. One example is a clinical trial phase I study for the delivery of a siRNA-containing liposomal formulation against EphA2 (Ephrin type-A receptor 2) to solid tumors (NCT01591356) [163].…”
Section: Assessing Rnai Delivery For Gbm Treatmentmentioning
confidence: 99%
“…[1][2][3][4][5] A pioneering study by Savic et al reported on spherical micelles self-assembled by fluorescently labeled poly(ethylene oxide)-b-poly(ε-caprolactone) (PEO-b-PCL) and investigated their intracellular distribution, providing a biological basis for polymeric nanoparticles as intracellular drug delivery vehicles. 6 Since then, much of the research has focused on the investigation of spherical nanoparticles.…”
Section: Introductionmentioning
confidence: 99%